PENGARUH STRATEGI PEER TUTORING UNTUK MENINGKATKAN MAHARAH KALAM SISWA KELAS XI MA MIFTAHUL ULUM PUNTIR-PURWOSARI - maulidiyah, lutfi lailatul (Lugatuna : Jurnal Prodi PBA, 2024)
Learning Arabic in Class XI MA Miftahul Ulum Puntir-Purwosari especially in speaking Arabic even though using text in the form of kalam has not succeeded in achieving the expected goals, this can be seen from the value of student learning outcomes which are still below the minimum completeness criteria. Based on the problems faced, the right solution to be applied in learning is a strategy that can stimulate students to speak Arabic. Based on the above, the researcher is interested in taking research with the title "The Influence of Peer Tutoring Strategies to Improve Maharah Kalam Class XI Students of MA. Miftahul Ulum Puntir – Purwosari. Based on these assumptions, the following problems can be formulated: (1) How is the ability to speak Arabic of class XI students of MA Miftahul Ulum Puntir-Purwosari before and after using the peer tutoring strategy (2) How does the peer tutoring strategy affect the students' Arabic speaking skills XI MA Miftahul Ulum Puntir-Purwosari? This study uses a quantitative approach in which this is to find out experimentation and the influence of peer tutoring strategies and research instruments used to input research data including tests and documentation From the results of this study, this study raised two research variables, namely peer tutoring strategy as the independent variable (X) and Maharah Kalam learning as the dependent variable (Y). Data on student learning outcomes were obtained by pretest in the form of working on questions and protesting by answering various questions from researchers, so it can be concluded that there is a positive correlation between the dependent variable and the independent variable.This relationship is classified as a strong relationship, because the calculated r values range from 0.61 to 0.80. So the hypothesis in this study can also be accepted. In terms of influence the peer tutoring strategy to maharah kalam class XI MA. Miftahul Ulum Puntir - Purwosari. Keywords learning strategy,peer tutoring,maharah kalam